MELEJITKAN KOMPETENSI PEDAGOGIK DAN PROFESIONAL GURU PPKn SMP DI KOTA PALU - Muliana Muliana (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2019)
The existence of the Teacher and Lecturer Law will enable teachers to have a strong position like other professions, so that it is possible for pedagogical competence and teacher professional competence to increase along with the certification process that has been enacted. The purpose of this study was to describe the level of mastery of pedagogical competence of PPKn teachers in SMP in Palu City, and to describe the level of mastery of professional competency of PPKn teachers at SMP in Palu City. The research method used is a qualitative approach, then to obtain data in accordance with the problem, data collection techniques are done by observation, questionnaires, interviews, and documentation. Then proceed with data analysis. The results and findings of the study show that the pedagogical competencies of PPKn teachers in junior high schools in Palu are generally classified as moderate and quite good, except for the learning aspects that educate there are some aspects that are not yet well mastered. Furthermore, the professional competencies possessed by PPKn SMP teachers in Palu City are generally quite high with some findings through questionnaires and interviews.